A rare cause of stroke: fail-implanted venous port catheter system – a case report - Yeniguen, Mesut (BMC Neurol, 2021)
BACKGROUND: We present the case of a 75-year-old female with acute embolic cerebral infarction caused by a fail-implanted venous port catheter system in the left subclavian artery. CASE PRESENTATION: A 75-year-old woman presented to our emergency room after acute onset of a right-sided hemiparesis and dysarthria. Within 2 days after admission, she developed a left-sided hemiparesis, ataxia with concordant gait disturbance and incoordination of the left upper limb. DWI-MRI showed acute multiple infarcts in both cerebral and cerebellar hemispheres. Laboratory examination, 24-h Holter electrocardiography and transthoracic echocardiography provided no pathological findings. Further examination revealed an arterially fail-implanted port catheter, placed in the left subclavian artery with its tip overlying the ascending aorta, as the source of cerebral embolism. CONCLUSION: This is the first case report of thromboembolic, cerebral infarction due to a misplaced venous port catheter in the subclavian artery, emphasizing the imperative need for a thorough diagnostic workup, when embolism is suspected but cannot be proven at first glance.